Teachers’ In-Service Trainings To Enhance Digital Pedagogy Skills In The Algerian University: Between Reality And Expectations - Hakkoum, Khaoula (Migration Letters, 2024)
To customize universities to the 21st C educational needs and requirements, both teachers and learners have been demanded to expand their knowledge of digital technologies. Digital literacy is one among the most emphasized skills in the 21st C notably with the massive changes the Covid-19 Pandemic has brought to teaching/learning concepts. Nowadays, teachers have shifted to online or flipped classrooms by means of necessity more than choice. Therefore, teachers have found it inevitable to rai[1]se the digital pedagogy literacy, which necessitates intensive in-service training on both using digital technologies and online teaching. The new reality imposed by the afore-mentioned changes urged teachers not only to use digital technologies but also to use them properly; however, a number of studies monitor that teachers lack digital pedagogy skills in the first place. The findings of these studies highly accentuate the need for in-service teacher’s trainings. For the purpose of this study, a questionnaire is administered to 20 teachers from different Algerian universities to examine teachers’ digital literacies skills level, check the effectiveness teachers in-service training and the teachers’ attitudes towards this problematic issue.